Quantifying the risk of insertion-related peritoneal dialysis catheter complications following laparoscopic placement: Results from the North American PD Catheter Registry. Issue 2 (March 2020) - Oliver, Matthew J; Perl, Jeff; McQuillan, Rory; Blake, Peter G; Jain, Arsh K; McCormick, Brendan; Yang, Robert; Pirkle, James L; Fissell, Rachel B; Golper, Thomas A; Shen, Jenny I; Hu, Susie L; et al.
Background: Peritoneal dialysis (PD) is a more cost-effective therapy to treat kidney failure than in-center hemodialysis, but successful therapy requires a functioning PD catheter that causes minimal complications. In 2015, the North American Chapter of the International Society for Peritoneal Dialysis established the North American PD Catheter Registry to improve practices and patient outcomes following PD catheter insertion. Aims: The objective of this study is to propose a methodology for defining insertion-related complications that lead to significant adverse events and report the risk of these complications among patients undergoing laparoscopic PD catheter insertion. Methods: Patients undergoing laparoscopic PD catheter insertion were enrolled at 14 participating centers in Canada and the United States and followed using a Web-based registry. Insertion-related complications were defined as flow restriction, exit-site leak, or abdominal pain at any point during follow-up. We also included infections or bleeding within 30 days of insertion, and any immediate postoperative complications. Adverse events were categorized as PD never starting or termination of PD therapy, delay in the start of PD therapy or interruption of PD therapy, an emergency department visit or hospitalization, or need for invasive procedures. Cause-specific cumulative incidence functions were used to estimate risk. Results: Five hundred patients underwent laparoscopic PD catheter insertion between 10 November 2015 and 24 July 2018. The cumulative risk of insertion-related complications 6 months from the date of insertion that led to an adverse event was 24%. The risk of flow restriction, exit-site leak, and pain at 6 months was 10.2%, 5.7%, and 5.3%, respectively. PD was never started or terminated in 6.4% of patients due to an insertion-related complication. Leaks and flow restrictions were most likely to delay or interrupt PD therapy. Flow restrictions were the primary cause of invasive procedures. Fifty percent of the complications occurred before the start of PD therapy. Conclusions: Insertion-related complications leading to significant adverse events following laparoscopic placement of PD catheters are common. Many complications occur before the start of PD. Insertion-related complications are an important area of focus for future research and quality improvement efforts.